THE ROLE OF SOCIAL WORKER AT SUB-DISTRICT LEVEL IN STRENGTHENING ENTREPRENEURSHIP OF KUBE TO OVERCOME CULTURAL POVERTY - Sariningsih, Yuce; Anwar, Ali; Wanda Kiyah George Albert (Lembaga Penelitian Universitas Pasundan, 2025)
The Ministry of Social Affairs implemented the KUBE (Kelompok Usaha Bersam) or known as micro business group which is managed and owned by beneficiaries of the Family Hope Program/Program Keluarga Harapan (PKH) by developing home business. This activity is accompanied by social work in sub district level under the coordination of Board of Social Service Regency with the duties and roles as person in charge during implementing the program for strengthening their entrepreneurship spirit so that they do not depend anymore on public assistance, this dependency is a manifestation of the culture of poverty. The aim is to describe the role of social work in strengthening entrepreneurship of KUBE. Research method used qualitative and data collection through interview. Data analysis used SWOT analysis to discover the appropriate strategy. The results showed that the role of social work in business supervising as an enabler, broker, mediator and educator need to be improved. The recommendation goes to institution related to KUBE development, higher education, community agent and Corporate Social Responsibility Program to strengthen the knowledge of social worker in micro business to improve spirit of social entrepreneurship and their business management. The role of social worker was very important to break cultural barrier in business development. Keywords: Cultural Poverty, Home Business, KUBE, Entrepreneurship, Social Worker